RE: Prevalence of MRI Lesions in Men Responding to a GP-Led Invitation for a Prostate Health Check: A Prospective Cohort Study - Alice Thomson; Haidar Al Saffar; Marlon Perera; Declan G. Murphy (Société Internationale d’Urologie Journal)
Controversy surrounds population-based screening for prostate cancer, which has typically relied on PSA level for risk stratification. This commentary examines the recent prospective trial examining the use of biphasic prostate MRI scans as a screening tool for prostate cancer. Using a reliable test, such as MRI prostate, at an earlier point along the diagnostic pathway, the authors provide a novel solution to a difficult problem. Further research is warranted to assess how biphasic MRI might be feasible at a population level.